Revolutionizing Insurance Sector in India: A Case of Blockchain Adoption Challenges - Saeed, Maryam; Arshed, Dr Noman (International Journal of Contemporary Economics and Administrative Sciences, 2022)
Background: Insurance concept was found numerous centuries before Christ (BC). Correspondingly, Chinese and Babylonian traders practiced moving or dispensing risks in 2nd and 3rd millennia BC. Now a days, insurance is the backbone of the economy but developing economies are facing challenges in increasing their penetration. The recent introduction of Big Data, IoT and InsurTech led to fourth industrial revolution in insurance in the developed world. Objective: This study aims to explore the challenges and solutions in adopting blockchain technology to increase insurance penetration in India. Research Methodology: This study applied a systematic literature review (SLR) to extract the themes/variables relating to challenges and solutions in adopting big data analytics in India's insurance sector. Several keywords were used to search relevant literature from Google Scholar. Based on inclusion and exclusion criteria, the filtered studies were explored. Findings: This study listed several challenges and their solutions in the adoption of blockchain technology in Indian insurance industry. Policymakers could adapt to the suggestions provided in improving the service delivery insurance sector